Increasing the efficiency of conservation spending: the case of payments for environmental services in Costa Rica - Engel, S.; Wunscher, T.; Wunder, Sven (Verlag Kessel, 2007)
Payments for environmental services (PES) are an increasingly used instrument both for financing and implementing conservation. The Costa Rican national PES scheme is often considered as a leading model in this regard. We find that improved targeting could substantially increase the efficiency of the program, in the sense that total environmental services achieved with a given budget were found to nearly double when environmental benefits, threat, and participation costs are considered in site selection. The results have implications for an upscaling of PES or the selection among potential conservation projects more generally. Nevertheless, targeting involves implementation costs and faces scientific, administrative and political challenges. Promising approaches for overcoming these challenges include: development of simple targeting tools; improved data availability; implementing targeting from the very start of a program; and using auctions to elicit participation costs.